Abrupt disturbance effect and treatment of large-section multi-arch tunnel under biased pressure: Based on field investigation - Jinxing Lai; Jiawei Xu; Peilong Yuan; Guanhua Cui; Yibo Zhang (Tunnelling and Underground Space Technology, 2027)

The mediator subunit PagMED20 is associated with enhanced vegetative growth and photosynthetic performance in poplar - Xiao Wang; Changwen Xu; Ce Zhang; Xuandong Liu; Binghe Wang; Yanjun Li; Jinxing Lin; Yaning Cui (Journal of Plant Physiology, 2026)

Seepage characteristics and transformation mechanisms of point–linear–planar infiltration in loess tunnels - Guanhua Cui; Junling Qiu; Jinxing Lai; Kunjie Tang; Jiawei Xu; Hao Sun (Tunnelling and Underground Space Technology, 2026)

Disturbance-driven reorganization of microbial and physical controls on soil organic carbon in karst soils - Ansa Rebi; Guan Wang; Irsa Ejaz; Rashda; Adnan Mustafa; Ahmed Salah Elrys; Mohsin Mahmood; Tao Yang; Mei Zhang; Xinglei Cui; Jinxing Zhou (CATENA, 2026)

Extracellular polymeric substances regulate depth-and-season-dependent soil organic carbon stabilization under prescribed fire in karst soils - Qilin Yang; Ansa Rebi; Tao Yang; Chenghao Zheng; Yang Rongkang; Yang Yuanli; Xinglei Cui; Jinxing Zhou (Journal of Environmental Management, 2026)

Beyond static structure: high-throughput chemical cartography of dynamic cell wall assembly - Yaning Cui; Xi Zhang; Shuizhong Wang; Weiqian Wu; Jinxing Lin (Trends in Plant Science, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

DMSO intercalation tunes antibiofouling properties of MXene/PVDF composite membranes: Toward sustainable wastewater treatment - Chenhong Cheng; Yuanyuan Zhang; Haochuan Yang; Jie Zhang; Linlin Yang; Rubing Dong; Jiayi Cui; Yongli Qin; Xueye Wang; Xingran Zhang; Jinxing Ma; Junjian Zheng (Journal of Environmental Chemical Engineering, 2026)

Clipping-and-burning alters carbon and nitrogen cycling through bacterial fixation pathways in the key Chinese karst region - Ansa Rebi; Guan Wang; Tao Yang; Irsa Ejaz; Adnan Mustafa; Jasper Kanomanyanga; Mohsin Mahmood; Xinglei Cui; Jinxing Zhou (Journal of Environmental Management, 2026)

Disasters caused by underground water pipe leakage in Chinese cities: Failure modes, influencing factors and prevention countermeasures - Jiawei Xu; Jinxing Lai; Junling Qiu; Haidong Jiang; Hao Sun; Jinzhao Tang; Guanhua Cui (Tunnelling and Underground Space Technology, 2026)

The role of Cu precursors and reaction mechanism for Cu/IM-5 hierarchical molecular sieve in NH3-SCR - Xinwei You; Zhifang Li; Wenyao Tan; Zhengzhong Cheng; Yuanyuan Ma; Qianhua Song; Jinxing Cui (Journal of Environmental Chemical Engineering, 2025)

Pulled GA signal orchestration proteome reconfiguration and redundancy cycling via PtGA2ox10-mediated metabolic gatekeeping in Chinese pine seeds - Xinxiu Zuo; Shuai Liu; Yanjun Li; Yanyan Zhang; Duxian Lu; Shihui Niu; Xiaojuan Li; Jinxing Lin; Yaning Cui (Plant Cell Reports, 2025)

Influence of fissure-induced linear infiltration on the evolution characteristics of the loess tunnel seepage field - Junling Qiu; Guanhua Cui; Jinxing Lai; Kai Zhao; Kunjie Tang; Lei Qiang; Ding Jia (Tunnelling and Underground Space Technology, 2025)

Highly efficient electrochemical reduction of nitrate to ammonia by a CuO-Co3O4 composite membrane electrode - Yufeng Wu; Shiyang Feng; Kui Yang; Wenjian Yang; Chao Li; Xuejun Cui; Jinxing Ma (Chemical Engineering Journal, 2025)

Research on the preparation of antimicrobial material based on thermoplastic polyurethane and drug release control - Chengzhi Cui; Jinxing Cao; Jianlan Liu; Hui Zhang (Drug Delivery and Translational Research, 2025)

Development and characterization of 40 InDel markers from the major histocompatibility complex genes of largemouth bass (Micropterus salmoides) - Meng Zhang; Zerui Wang; Jiao Cui; Xiao Ma; Zhigang Qiao; Xianghui Kong; Ruwei Xu; Shengjie Li; Jinxing Du; Chunlong Zhao (Molecular Biology Reports, 2024)

Single-cell characterization of major components of plant cell walls in situ by Raman spectroscopy - Yujian Li; Weiwei Shen; Xi Zhang; Yaning Cui; Yuanyuan Zhao; Yayu Guo; Xiaojuan Li; Shuizhong Wang; Guoyong Song; Pu Wang; Jianfeng Ma; Jinxing Lin (Science China Life Sciences, 2024)

Fabrication of wide temperature FexCe1-xVO4 modified TiO2-graphene catalyst with excellent NH3-SCR performance and strong SO2/H2O tolerance - Zhifang Li; Qian Zhang; Jian Yang; Yueyu Li; Jinxing Cui; Yuanyuan Ma; Changlong Yang (Environmental Science and Pollution Research, 2022)

Effects of secondary succession on soil fungal and bacterial compositions and diversities in a karst area - Genzhu Wang; Yuguo Liu; Ming Cui; Ziyuan Zhou; Qian Zhang; Yajin Li; Wenxiu Ha; Danbo Pang; Jiufu Luo; Jinxing Zhou (Plant and Soil, 2022)

Development and characterization of 37 SNP markers for the largemouth bass (Micropterus salmoides) by using PCR–RFLP method - Zhou Jiang; Jiao Cui; Jiaqi Shao; Chuanju Dong; Jinxing Du; Yubang Shen; Shengjie Li; Meng Zhang; Xuejun Li (Conservation Genetics Resources, 2021)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Influence of different preparation methods on the activity of Ce and Mo co-doped ZSM-5 catalysts for the selective catalytic reduction of NOx by NH3 - Zhifang Li; Jian Yang; Yadong Zhou; Jinxing Cui; Yuanyuan Ma; Cui Geng; Yan Kang; Jiayin Liu; Changlong Yang (Environmental Science and Pollution Research, 2020)

Techniques for detecting protein-protein interactions in living cells: principles, limitations, and recent progress - Yaning Cui; Xi Zhang; Meng Yu; Yingfang Zhu; Jingjing Xing; Jinxing Lin (Science China Life Sciences, 2019)

Competition and habitat filtering jointly explain phylogenetic structure of soil bacterial communities across elevational gradients - Qian Zhang; Marta Goberna; Yuguo Liu; Ming Cui; Haishui Yang; Qixiang Sun; Heribert Insam; Jinxing Zhou (Environmental Microbiology, 2018)
Summary The importance of assembly processes in shaping biological communities is poorly understood, especially for microbes. Here, we report on the forces that structure soil bacterial communities along a 2000 m elevational gradient. We characterized the relative importance of habitat filtering and competition on phylogenetic structure and turnover in bacterial communities. Bacterial communities exhibited a phylogenetically clustered pattern and were more clustered with increasing elevation. Biotic factors (i.e., relative abundance of dominant bacterial lineages) appeared to be most important to the degree of clustering, evidencing the role of the competitive ability of entire clades in shaping the communities. Phylogenetic turnover showed the greatest correlation to elevation. After controlling the elevation, biotic factors showed greater correlation to phylogenetic turnover than all the habitat variables (i.e., climate, soil and vegetation). Structural equation modelling also identified that elevation and soil organic matter exerted indirect effects on phylogenetic diversity and turnover by determining the dominance of microbial competitors. Our results suggest that competition among bacterial taxa induced by soil carbon contributes to the phylogenetic pattern across elevational gradient in the Tibetan Plateau. This highlights the importance of considering not only abiotic filtering but also biotic interactions in soil bacterial communities across stressful elevational gradients.

Novel FBN1 mutations are responsible for cardiovascular manifestations of Marfan syndrome - Jin’e Wang; Yupeng Yan; Jinxing Chen; Ling Gong; Yu Zhang; Mengmeng Yuan; Bing Cui; Yibo Wang (Molecular Biology Reports, 2016)

Trend of water resource amount, drought frequency, and agricultural exposure to water stresses in the karst regions of South China - Long Wan; Jinxing Zhou; Hongyan Guo; Ming Cui; Yuguo Liu (Natural Hazards, 2016)

Novel polymorphisms of goat growth hormone and growth hormone receptor genes and their effects on growth traits - Xiaopeng An; Lixin Wang; Jinxing Hou; Guang Li; Yuxuan Song; Jiangang Wang; Mingming Yang; Yihong Cui; Binyun Cao (Molecular Biology Reports, 2011)